An ultrathin SiO2 blocking layer to suppress interfacial recombination for efficient Sb2S3-sensitized solar cells. Issue 6 (20th April 2018) - Xu, Yafeng; Chen, Wenyong; Ding, Xihong; Pan, Xu; Hu, Linhua; Yang, Shangfeng; Zhu, Jun; Dai, Songyuan
Abstract : An SiO2 thin layer efficiently suppresses the recombination at the TiO2 /Sb2 S3 interface and enhances the photovoltaic performance of Sb2 S3 sensitized solar cells. Abstract : Interfacial charge recombination is a serious problem in semiconductor-sensitized solar cells which severely limits the power conversion efficiency. Herein, an ultrathin SiO2 blocking layer was introduced to the TiO2 surface to suppress the interfacial recombination in Sb2 S3 -sensitized solar cells. The SiO2 blocking layer was deposited by a simple chemical bath method. Due to the unique features of the SiO2 layer, the Sb2 S3 sensitizer shows a remarkable change in the morphology after SiO2 coating, forming numerous irregular large crystals which did not bring a negative impact. Electrochemical impedance spectra and open-circuit voltage-decay analysis confirm that the SiO2 layer efficiently suppresses the interfacial recombination at the TiO2 /Sb2 S3 interface which is the major recombination path in the solar cells. As a result, the device exhibits remarkably enhanced open-circuit voltage, fill factor and power conversion efficiency.